The effect of gut microbiota and insecticide resistance on host plant preferences and voracity of the cotton fly, Spodoptera littoralis - Dzemedzionaite, Vaida (2021)
To counteract pesticide resistance development, it is crucial to understand why and when it evolves. Additionally, to inform the farmers about this term and provide advices on efficient pest management strategies to prevent pesticide resistance. An agroecological approach may be suitable since it applies science, practice and social movements to improve more sustainable food systems by helping developing pest management strategies. The main aims of this project were gaining better knowledge about the possible connection between insecticide resistance development, host plant range and the effect of gut microbiota and surveying the knowledge among farmers on pesticide resistance development. The experimentations on the pest, Spodoptera littoralis, were performed to study if host plant preference and performance with insects that were either pesticide resistant or susceptible and where the gut microbiota was damaged while using the antibiotics or intact. The preference experiments did not show any results of changed host plant preference or survival rate due to resistance level or gut microbiota status. It was found that larvae’s initial host plant choice differs from the final choice indicating that larvae need to feed on the host plant longer to make a choice. However, while treated with the antibiotics, larvae ate significantly more of the leaves than unexposed larvae. Just as for the preference experiment, the efficiency of conversion experiment did not show significant differences in terms of resistance level or gut microbiota. A significant difference in efficiency of conversion was, however, found between the host plants where cotton presented higher indices compared to maize. In addition, larvae gained more weight consuming cotton than on maize, which indicates that maize is a poor host plant and that the host plant plays an important role in larval metabolism. The social science results indicated that farmers from Sweden, Tanzania and Lithuania are aware of pesticides detrimental effects but still use pesticides very actively, mainly because of their effectiveness. Tanzanian respondents were the only ones who have never heard about pesticide resistance while Swedish farmers presented high knowledge about this process. Better knowledge of pesticide use and pesticide resistance development need to be introduced to Tanzanian farmers to prevent the health problems caused by pesticide application. More sustainable pest management strategies in all the targeted countries are crucial to reduce pesticide use and pesticide resistance development. To do so, communication between researchers and farmers – practitioners is needed.